Enhancing SMEs Performance through Supply Chain Collaboration and moderation of Supply Chain Technology Implementation - Imtiaz, Muhammad (2023)
Goal: The minimal inter-firm resource sharing has raised problems for small and medium-sized enterprises (SMEs). There has been little focus on a thorough understanding of supply chain collaboration in the context of SMEs in Pakistan. This research looks into the antecedent impact of governance mechanisms and collaborative culture on supply chain collaboration (SCC), as well as the direct influence of supply chain collaboration on SMEs' performance in developing countries. Design/Methodology/Approach: The data was collected using a closed-ended questionnaire from randomly selected respondents from Pakistani SMEs. SMART PLS 3.0 software is utilized for statistical analysis. Results: The findings showed a significant positive link between SCC and the performance of small businesses. Moderation was investigated between the variables. This means that supply chain technology Implementation (as moderator) is a process that provides SMEs to improve collaboration between partners through information and advanced manufacturing technology and provide suitable solutions to achieve performance. Limitations of the investigation: It is a cross sectional study and front line managers are eliminated from the study, however they are also the key respondents of supply chain (SC) implementation. Implications: The implications of this research for SC managers and researchers involved in supply chain collaboration adoption in SMEs are important. Originality/ Value: Findings supported the concept that if the organization has a supportive culture towards supply chain collaboration adoption then SMEs will improve their performance.